Impact of Liquidity on Rural and Community Banks Profitability in The Eastern Region of Ghana - Osumanu Alhassan; Oscar Opoku Agyemang Opoku (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
Despite the major role played by rural and community banks in economic development and in the financial climate, their performance over a decade now have not been up to expectations. They continue to experience huge challenges due to innovations in technology as well as globalization which create opportunities for growth. The study was to examine the impact of liquidity on rural and community banks in the Eastern Region of Ghana selected from eleven (11) banks for the period of ten years from 2007 – 2016. The study used panel data and secondary data to collate the ratios from all the selected rural and community banks. A regression model was developed with Return on Asset as the dependent variable accompanied with other six explanatory variables. It was revealed that quality of loan portfolio ratio; capital ratio and loan to total assets had significant and positive relationship with profitability. It was also revealed that shocks in all the liquidity variables had one or other implications on profitability. Finally, based on finding seven, which states that cost to income has negative and significant effect on profitability, the study recommended that management must adopt information and communication technology to reduce cost and easy access to banks’ product in the form of Automated Teller Machine.